2017
DOI: 10.4103/aer.aer_10_17
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation in chronic pain: A meta-analysis

Abstract: Background:In this meta-analysis, we explore the role of repetitive transcranial magnetic stimulation (rTMS), a noninvasive neuromodulation technique in the treatment of chronic pain.Methods:Studies comparing rTMS and conventional treatment for chronic pain were searched. The comparison was made for decrease in the pain scores with and without (sham) the use of rTMS after a follow-up interval of 4–8 weeks. All reported pain scores were converted into a common scale ranging from “0” (no pain) to “10” (worst pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
3
26
1
2
Order By: Relevance
“…44,45 This technique has emerged in recent years as an interesting and promising new treatment for pain. 29,[46][47][48][49] The efficacy of high-frequency rTMS over the M1 on chronic neuropathic pain that is resistant to drugs has already been demonstrated in previous studies conducted on a range of diseases. [50][51][52][53][54][55][56][57][58][59][60][61] In general, the clinical effect begins a few days after the end of the rTMS cycle, lasts less than a week after a single stimulation session, and 2-3 weeks after repeated cycles of rTMS.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…44,45 This technique has emerged in recent years as an interesting and promising new treatment for pain. 29,[46][47][48][49] The efficacy of high-frequency rTMS over the M1 on chronic neuropathic pain that is resistant to drugs has already been demonstrated in previous studies conducted on a range of diseases. [50][51][52][53][54][55][56][57][58][59][60][61] In general, the clinical effect begins a few days after the end of the rTMS cycle, lasts less than a week after a single stimulation session, and 2-3 weeks after repeated cycles of rTMS.…”
Section: Discussionmentioning
confidence: 87%
“…In general, the clinical effect begins a few days after the end of the rTMS cycle, lasts less than a week after a single stimulation session, and 2‐3 weeks after repeated cycles of rTMS . This beneficial effect observed after repeated stimulation is a key factor that warrants being able to administer this treatment in clinical practice, even though it has yet to be characterized more thoroughly . Furthermore, rTMS may prove effective in the treatment of neuropathic pain with a central genesis by modulating, at the level of the cortex, the activity of related sub‐cortical circuits of the brain areas involved in pain processing (such as the thalamus, the anterior cingulate cortex and the orbital‐frontal region) that modulate the emotional component of pain, and by facilitating the inhibitory mechanisms of the descending pain pathway at the periaqueductal gray (PAG) level .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, high‐frequency rTMS of SMA can be a suitable target for PD FOG . For other nonmotor symptoms, high‐frequency rTMS of M1 is a potential treatment for PD‐related chronic pain . Although one study did not show synergistic effects of sequential high‐frequency stimulation of M1 and DLPFC, other combination targets are still worth trying.…”
Section: Noninvasive Brain Stimulation In Pdmentioning
confidence: 99%
“…108 For other nonmotor symptoms, high-frequency rTMS of M1 is a potential treatment for PD-related chronic pain. 109 Although one study did not show synergistic effects of sequential high-frequency stimulation of M1 and DLPFC, 104 other combination targets are still worth trying. Because M1 cortical excitability studies showed increased facilitatory intracortical circuit (short interval intracortical facilitation), decreased SICI, and imaging studies showed decreased activities in motor associated area, such as the SMA, combined low-frequency rTMS of M1 with high-frequency rTMS of SMA or the premotor cortex could be a treatment option.…”
Section: Future Outlook For Rtms As Treatment For Pdmentioning
confidence: 99%